Synergy between Religion and Science: A Contemporary Christian Review with Evidence from Ethiopia’s COVID 19 Response and Male Circumcision Rite - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2026)
The conflict narrative between religion and science persists in popular discourse despite growing historical and theological evidence of compatibility. Contemporary Christian theology offers a framework for synergy, yet empirical case studies from non‑Western contexts remain underexplored. This review critically examines the theological foundations for science‑religion synergy within mainstream contemporary Christianity and analyses two Ethiopian case studies Orthodox faith leaders’ role in COVID‑19 vaccination promotion, and the male circumcision rite to demonstrate synergy in practice. A critical review synthesising peer‑reviewed literature, theological documents, public health reports, and qualitative studies on Ethiopian Orthodox Christian engagement with science. Contemporary Christian theology (Catholic, Orthodox, mainline Protestant) provides robust support for synergy via complementary domains of “how” (science) and “why” (faith). In Ethiopia, faith leaders actively promoted COVID‑19 vaccination using the message “God protects us from death through faith and science,” receiving training and publicly modelling vaccination. Male circumcision, a near‑universal cultural rite of passage (not a sacrament), has been harmonised with medical science, with Church endorsement of hospital‑based procedures. Commonalities include faith leaders reframing practices as science‑consistent, partnership with health authorities, and adaptive use of religious authority. Synergy between religion and science is not an abstract ideal but a lived, effective partnership capable of saving lives and preserving cultural identity. The Ethiopian Orthodox model offers a replicable paradigm. Public health programmes should actively partner with trusted religious leaders. Theological education should embrace science engagement. Comparative research across Orthodox traditions and quantitative impact studies are urgently needed.